Customer Loyalty in Digital Banking: The Role of User Journey and Customer Experience (A Case Study on Bank MAS Mobile) - Khoiriyah Nurul Yusdasani; Karto Adiwijaya (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the role of user journey and customer experience in influencing customer loyalty within the context of digital banking services, using Bank MAS as a case study. The research model adopts a quantitative approach by employing the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method on data collected from 280 respondents who use the Bank MAS Mobile application. The variables tested include ease of use, perceived value, quality of support, reliability, perceived risk, and ability to innovate as factors influencing customer experience, along with the role of customer satisfaction as a mediating variable toward customer loyalty. The findings reveal that all independent variables significantly affect customer experience, with ability to innovate emerging as the most dominant factor. Furthermore, customer satisfaction is proven to mediate the relationship between customer experience and customer loyalty. This study contributes theoretically to the development of customer experience models in the local digital banking context and offers managerial implications for enhancing innovation and service quality in the digital banking sector.